THE USE OF THE GENETIC PANEL TO DIAGNOSE AMYOTROPHIC LATERAL SCLEROSIS (ALS) - Patricio da Silva Lemos, Margot; Ost Gomes, Marylha; Siqueira Rocha, Gisele; Karolini Walger Schultz, Leticia (Journal of Interdisciplinary Debates, 2022)
Amyotrophic Lateral Sclerosis (ALS) represents the most common form of Motor Neuron Disease (MND), which is more frequent in adults and the elderly. The degenerative process of this disease has a complex etiology and is related to several factors. Its symptoms develop from a successive loss of both upper motor neurons (LMN), located in the cerebral cortex, and lower motor neurons (LMN), located in the brainstem and anterior horn of the spinal cord. Its diagnosis is often delayed and its prognosis is not favorable. This work reviewed data on ALS and the Genetic Panel Test arranged in physical and electronic media such as books, virtual libraries and databases. The findings of this study indicate that the genetic panel is extremely important for patients with amyotrophic lateral sclerosis, since it allows the specific evaluation of the genes involved in this disease and their possible gene mutations, in addition to allowing the differentiation in their hereditary and sporadic.